Cryopreserved equine umbilical cord tissue allograft characterization and biocompatibility in vivo in musculoskeletal tissues: a controlled study - Alicia L. Bertone; Craig Reinemeyer; George Tsaprailis; Daniel Ragland; Britta Leise (BMC Medicine)
Abstract Background The use of micro-particulate allografts is rising, but knowledge about the protein characterization and biocompatibility of umbilical cord-derived allografts (UC) in vivo is limited. Methods Proteomic analyses using mass spectrometry (MS) determined equine UC protein relative quantification and functions using total spectral counts (TSC). UC cytokines were quantified by enzyme-linked immunosorbent assay (ELISA). Three in vivo studies assessed recipient clinical and tissue biocompatibility in joints and ligaments. Results Proteomics revealed 2645 annotated TSCs. Proteins of > 89 TSC were considered abundant and were present in all donors. Proteins within the same donor had a 4.7% mean variation. Inflammatory cytokines were low in UC. In vivo, the prospective randomized, masked, controlled study in carpal joints and ligaments of clinically normal horses had median scores of 0 (none) for lameness and pain for 42 days. Synovial fluid showed a transient transudative synovitis after UC injection that was greater than baseline and control and returned to normal after day 5 (P < 0.001). Synovial fluid inflammatory cytokines were low; however, the anti-inflammatory cytokines Il-1ra, Il-10, and Il-1ra/Il-1 ratio were greater after UC injection than at baseline and control (P < 0.001). Blood hematology, chemistries, and serum amyloid A did not reveal systemic effects. The in vivo study of osteoarthritis and desmitis/tendonitis improved in lameness and pain over a 28-day study and had parallel synovial fluid results to the normal horse study, also without adverse events. The in vivo pathologic study evaluated joint and ligament tissues 2 and 5 days after injection and corresponding lymph nodes for evidence of the allograft or inflammation. The synovial membrane, articular cartilage, and lymph nodes were histologically normal, except for mild inflammation in the injection tracts. Conclusions Well-defined proteins were consistently present in different donors and within batches. Proteins included fibrillar and glycan proteins with a variety of roles and regulatory functions in the connective tissue matrix. The rise in Il-1ra and high Il-1ra/Il-1 ratio after UC injection could block the catabolic effect of Il-1. No adverse events were observed. Within the limits of this study, UC was safe for injection into joints and ligaments in clinically normal horses.